Bilan de pratiques évaluatives des apprentissages à distance en contexte de formation universitaire - Isabelle Nizet; Julie Lyne Leroux; Colette Deaudelin; Sébastien Béland; Jean Goulet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The development of distance learning in higher education raises the question of the nature and validity of evaluation practices of teachers in a context where the nature of the collected data, the scope and credibility of their interpretation and the procedures to communicate results to the students remain subject to requirements framed by collective standards. To enlighten the institutional choices about distance learning evaluation in the faculties of the Université de Sherbrooke, a survey of evaluation practices was conducted through focus groups of 25 participants from its nine faculties, and who agreed to participate in the research. The results of this survey are presented along with their analysis in the light of a review of writings concerning the typology of the instruments used.